Is there a EU copyright jurisprudence?: an empirical analysis of the workings of the European Court of Justice - Favale, Marcella; Kretchmer, Martin; Torremans, Paul (Centre for Copyright and New Business Models in the Creative Economy, 2015)
The Court of Justice of the European Union (ECJ) has been suspected of carrying out a harmonising agenda over and beyond the conventional law-interpreting function of the judiciary. This study aims to investigate empirically two theories in relation to the development of EU copyright law: (i) that the Court has failed to develop a coherent copyright jurisprudence (lacking domain expertise, copyright specific reasoning, and predictability); (ii) that the Court has pursued an activist, harmonising agenda (resorting to teleological interpretation of European law rather than – less discretionary – semantic and systematic legal approaches).